Migration and Cross-Border Financial Flows - Maurice Kugler; Oren Levintal; Hillel Rapoport (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
The gravity model has provided a tractable empirical framework to account for bilateral flows not only of manufactured goods, as in the case of merchandise trade, but also of financial flows. In particular, recent literature has emphasized the role of information costs in preventing larger diversification of financial investments. This paper investigates the role of migration in alleviating information imperfections between home and host countries. We show that the impact of migration on financial flows is strongest where information problems are more acute (that is, for more informational sensitive investments and between more culturally distant countries) and for the type of migrants that are most able to enhance the flow of information, namely, skilled migrants. We interpret these differential effects as additional evidence pointing to the role of information in generating home-bias and as new evidence of the role of migration in reducing information frictions between countries.
Keywords: F21; F22; O1; 330; Migration; international financial flows; international loans; gravity models; information asymmetries